Recent Developments In Surgery Laser - Ansari, Maulana Mohd. (Indian Journal of Community Health, 1997)
Laser is one of the few recent developments in surgery that need clear understanding not only by the medical students and professionals but also by the public at large which constitutes the subject of surgery. Laser, first successfully developed by Americans in 1960 is an acronym that stands for Light Amplification by Stimulated Emission of Radiation[1]. Lasers utilize high energy waves within the electromagnetic spectrum to produce heat for the surgical effects of cutting, ablation (vaporization) and coagulation[2]. Lasers work on the principle of Radiation Heat Transfer, i.e., the laser beams contain no inherent heat and the electrodes of "bovie" units are not hot. They both transmit radiation energy. Heat is created only when the tissue absorbs the transmitted radiation and converts it to motion in its atoms and molecules. This is exactly the way a microwave oven works only at different frequencies.